2022
DOI: 10.1002/jssc.202200187
|View full text |Cite
|
Sign up to set email alerts
|

Trace determination of imidacloprid and its major metabolites in wheat‐soil system

Abstract: Trace analysis method is a reliable basis for studying the translocation and metabolism of imidacloprid used as an insecticide in wheat, and it clarifies whether biologically active metabolites including residual imidacloprid, have long-lasting insecticidal potency against wheat aphids under seed treatment during the entire growth period. In this study, a highly sensitive analytical method was established to determine the residues of imidacloprid and its six metabolites(5-hydroxy imidacloprid, imidacloprid ole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…However, they were inefficient at removing chlorophyll and pigments. Regarding the SPE cleanup methods, the Carb layer in the NH 2 /Carb and Carb SPE column contains GCB, which is efficient in removing chlorophyll, lutein, and other pigments . In this study, the NH 2 -Carb cartridges exhibited lower recovery for DN-CLO in leaf samples, possibly due to the –NH 2 groups of the cartridges interacting with the DN-CLO groups, impeding elution.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…However, they were inefficient at removing chlorophyll and pigments. Regarding the SPE cleanup methods, the Carb layer in the NH 2 /Carb and Carb SPE column contains GCB, which is efficient in removing chlorophyll, lutein, and other pigments . In this study, the NH 2 -Carb cartridges exhibited lower recovery for DN-CLO in leaf samples, possibly due to the –NH 2 groups of the cartridges interacting with the DN-CLO groups, impeding elution.…”
Section: Resultsmentioning
confidence: 74%
“…Regarding the SPE cleanup methods, the Carb layer in the NH 2 /Carb and Carb SPE column contains GCB, which is efficient in removing chlorophyll, lutein, and other pigments. 23 In this study, the NH 2 -Carb cartridges exhibited lower recovery for DN-CLO in leaf samples, possibly due to the −NH 2 groups of the cartridges interacting with the DN-CLO groups, impeding The efficiency of SPE depends on the type and volume of the elution solvent and, 26 thus in this study, different solvent volumes were tested (0, 2, 4, and 6 mL). The results showed that the recoveries of TMX and its metabolites were >80% when the eluent volume was 2 mL (Figure S3c).…”
Section: Optimization Of Sample Preprocessing 321 Extraction Procedurementioning
confidence: 76%
See 1 more Smart Citation
“…Imidacloprid and its six main metabolites (5-hydroxy imidacloprid, imidacloprid olefin, imidacloprid nitrosimine, imidacloprid guanidine, imidacloprid urea, and 6chloronicotinic acid) in wheat-soil systems including wheat leaves, wheat ears, roots, and soil were analyzed according to our previously developed method. 13 Briefly, each sample (5 g) was placed in a 50 mL centrifuge tube to which 100 μL of 2.5 mg/L imidacloprid-D 4 solution was added and vortexed for 1 min. Subsequently, the sample was extracted by 10.0 mL of an acetonitrile and water mixture (v/v = 80/20) by vigorously shaking for 5 min.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…Imidacloprid (IMI) is a commonly used systemic insecticide effective against plant aphids, white flies, and hoppers by seed treatment, foliar application, and soil treatment in many edible vegetables and staple crops. Specially, it is widely used as a seed coating agent, which exhibits a long-term control efficacy (e.g., 7 months) against wheat aphids, implying that the dosage and frequency of insecticide application could be reduced. In China, 10–15 million hectares are infested with cereal aphids, resulting in 10% yield losses annually, , where the wheat aphids Rhopalosiphum padi (Linnaeus) and Sitobion avenae (Fabricius) are the predominant pests on wheat crops . Surprisingly, previous studies reported that the concentration of imidacloprid in wheat leaves at the later growth stage was close to its LC 10 value for aphids under seed treatment, while the control effect against wheat aphids was still higher than 80%. , Therefore, it is interesting to understand how this insecticide possesses such an excellent long-term performance even at a very low concentration in plant levels; however, so far, the underlying mechanism is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%